Catalytic Isomerization of Unprotected Mesoionic N‐Heterocyclic Olefins and Their Lewis Adducts - Qu, Zheng‐Wang; Zhu, Hui; Streubel, Rainer; Grimme, Stefan (European journal of organic chemistry, 2022)
Recently, novel C5‐position‐unprotected mesoionic N‐heterocyclic olefins (mNHOs) demonstrated interesting reactivity with various Lewis acids during experiments. In this work, extensive DFT calculations show that the isomerization of such mNHOs to more Lewis‐basic mesoionic carbenes (MICs) can be efficiently catalyzed by weakly protic acidic species including C5‐unprotected mNHOs, their Lewis adducts and polar H2O molecules, thus enabling catalytic isomerization and H‐isotope exchange of such mNHOs and their Lewis adducts. Extensive DFT calculations show that the isomerization of C5‐unprotected mesoionic N‐heterocyclic olefins (mNHOs) to more Lewis basic mesoionic carbenes (MICs) can be efficiently catalyzed by weakly protic acidic species including unprotected mNHO, MIC, their Lewis adducts and polar H2O molecules, thus enabling catalytic isomerization and H‐isotope exchange reactions of such mNHOs and their Lewis adducts.